2023
DOI: 10.1111/pala.12672
|View full text |Cite
|
Sign up to set email alerts
|

A new method for extracting conodonts and radiolarians from chert with NaOH solution

Abstract: Microfossils are important components of sedimentary rocks used for palaeontological, biostratigraphic, palaeoenvironmental and palaeoclimatic investigations. They are usually extracted from rocks using an acid solution, which might vary depending on the embedding rock lithology. Here we propose a new method using common NaOH (sodium hydroxide; soda) to digest cherts (micro‐ and cryptocrystalline quartz) instead of the standard technique based on HF (hydrofluoric acid). This new method allows the collection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Recently, Rigo et al . 22 found that the solubility of chert in NaOH solutions increases markedly with increasing temperature. They reported the use of 3 mol/L NaOH at 80 °C to extract well-preserved conodonts from chert.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Rigo et al . 22 found that the solubility of chert in NaOH solutions increases markedly with increasing temperature. They reported the use of 3 mol/L NaOH at 80 °C to extract well-preserved conodonts from chert.…”
Section: Introductionmentioning
confidence: 99%
“…They reported the use of 3 mol/L NaOH at 80 °C to extract well-preserved conodonts from chert. Although most dissolution reactions of chert with NaOH do not occur at room temperature 21 , it may be possible to dissolve chert and obtain radiolarians at higher temperatures 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations